Financial constraint and output pricing: The case of international sanctions against Iran - Sajad Ebrahimi (Journal of Applied Economics, 2022)
This paper examines whether financial constraints of firms influence their pricing behavior. To do so, a product-level dataset is used from Iranian-listed manufacturing companies. This study employs the imposition of international sanctions against Iran in 2012 as an exogenous shock to identify the effect of financial constraints. According to the results financially restricted firms keep their prices lower than their counterparts to increase their internal financial resources. The results show the difference between output prices of constrained and unconstrained firms rising after the imposition of sanctions. In addition, this relationship is affected by the degree of export-orientation of firms, and only exporter firms that experienced the negative demand shock after the sanctions, set their price lower to reduce the financial pressures. Also, the degree of dependency on imported input does not play a significant role in the relationship and ownership structure of firms has a significant impact on the relationship.
Keywords: 330; exports; financial constraints; ownership structure; Price changes; sanctions